Letter to Mrs Campbell - Ball, William; Campbell, Mrs. (1908)
Typescript copy of a letter from William Ball to Mrs Campbell, wife of Major Alexander Campbell, giving an account of Major Campbell's last days in prison before his execution.
Manuscript reference no. : NLA MS 4516.
Typescript photocopies.
Original held by United Services Museum, H.Q. Scottish Command, The Castle, Edinburgh L.
William Ball was Chaplain and Inspector of the gaol at Armagh, Ireland at the time of Major Alexander Campbell's execution in 1908. Major Campbell was sentenced to death for his part in a duel with Captain Boyd.
Keywords: Ball, William -- Correspondence; Campbell, Alexander, -- -1908.; Clergy -- Ireland -- Correspondence; Executions and executioners -- Ireland; Clergy